Generalized Scheme For Fractal Based Digital Signature (GFDS). - Alia, Mohammad Ahmad; Samsudin, Azman (Dr. Sang H. Lee, 2007)
This paper describes a new development in the cryptographic digital signature scheme based on Mandelbrot and Julia fractal sets. Recently it has been shown that it is possible to have digital signature scheme based on fractal due to the strong connection between the Mandelbrot and Julia fractal sets.